2021
DOI: 10.52547/johe.10.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Anxiety among Healthcare Providers of COVID-19 Patients from March to May 2020, Rafsanjan County, Iran

Abstract: Article InfoBackground: Health concerns are among the major concerns of the staff dealing with infectious diseases, such as COVID-19. This study aimed to examine health anxiety (HA) in the healthcare workers (HCWs) of COVID-19 patients from March to May 2020. Material and Methods: The statistical population of this descriptive study consisted of all 101 HCWs of COVID-19 patients at Ali ibn-Abi Talib Hospital in the Rafsanjan County, who were invited to help with this survey using the census sampling method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…Consistent with this finding, Mousavi et al, who conducted relatively similar research to the present study, reported a rate of health anxiet y as moderate [5]. This finding was repeated in some other similar studies [20,21]. According to research conducted in recent years, the level of health anxiety in nurses was often reported to be between mild and moderate.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this finding, Mousavi et al, who conducted relatively similar research to the present study, reported a rate of health anxiet y as moderate [5]. This finding was repeated in some other similar studies [20,21]. According to research conducted in recent years, the level of health anxiety in nurses was often reported to be between mild and moderate.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, no significant gender disparity among health professionals, in terms of stress, was identified. Furthermore, Mirzabeigi, Agha Mohammad Hasani, Sayadi, Safarian, and Parand Afshar [ 60 ] support the results of our current study. Their study assessed health anxiety among healthcare personnel during the current pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Since our study was conducted on frontline nurses who directly cared for COVID patients, it is reasonable that the level of health anxiety in these nurses is high. Consistent with this finding, in other studies, the level of health anxiety of the medical staff, especially the frontline nurses, was high [ 9 , 17 , 18 , 50 ]. Frontline nurses face much more psychological stress due to their work environment.…”
Section: Discussionsupporting
confidence: 86%